Hook, line, and social media: crowd-sourced images reveal size and species patterns of ocean sunfishes (Tetraodontiformes, Molidae) from California to Alaska - Mowatt-Larssen, Tor; Thys, Tierney M.; Hildering, Jackie; Caldera, Eric J.; Biesack, Ellen E.; McDowell, Jan R.; Nyegaard, Marianne (Frontiers in Marine Science, 2025)
Taxonomic confusion and limited data have impeded species-level biogeographic analyses of the world’s largest bony fishes, ocean sunfishes (Molidae; ‘molids’), in many ecosystems. However, recent advances in molid taxonomy and the emergence of photo-based community-science platforms provide an opportunity to revisit species-level biogeography. In this study, we use crowd-sourced images of 1,213 ocean sunfishes to determine if molid morphology visible in citizen-science images permits reliable species determination. From the ensuing data, we describe patterns in molid size structure and species composition from 1,178 molids observed in the Alaska and California Current Systems (ACS and CCS, respectively). Molids <1 m total length (TL) were commonly reported in the CCS, particularly off the central coast of California, suggesting this area may function as a molid nursery. Molids >1 m TL were more commonly observed in both the CCS and cooler ACS, which suggests larger molids occupy a larger thermal range (ontogenetic habitat expansion) than smaller individuals. Overall, Mola mola was the most frequently observed species in both the ACS and CCS; however, the persistent occurrence of Mola tecta in both current systems suggests a range extension for this otherwise Southern Hemisphere species. The species identity of six M. tecta specimens from California and Alaska were verified with genetic analysis. Finally, two Mola alexandrini confirmed in the southern portion of the CCS represent the first records of this species in the Northeast Pacific Ocean.